2021
DOI: 10.1002/ente.202100644
|View full text |Cite
|
Sign up to set email alerts
|

Highly Graphitic N‐Doped Biomass‐Derived Hard Carbon with a Low Operating Potential for Potassium‐Ion Batteries

Abstract: Hard carbon is considered to be the most promising anode material for potassium‐ion batteries (PIBs) because of its high storage capability and inexpensive cost, but most of them have a high operating potential. Herein, a highly graphitic nitrogen‐doped hard carbon (NHC) is prepared by soaking a corn stalk in urea solution and calcination. NHC can deliver a reversible capacity of 402 mAh g−1 in the first charge–discharge cycle and 87% of the total capacity is measured below 1 V versus K+/K. Simultaneously, it … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 32 publications
1
3
0
Order By: Relevance
“…On the contrary, graphitic N sites display the weak adsorption of K + but enhance the conductivity of the carbon skeleton and promote the K-storage at a low potential range, which is beneficial for improving the energy density of PIBs . A similar potential effect from graphitic N sites was also observed by Chen et al who showed that for the prepared highly graphitic N-doped hard carbon, about 87% of capacity came from the contribution of the low potential region of below 1.0 V . In addition, significantly enhanced K + diffusion kinetics via reducing the diffusion energy barriers was also achieved in the prepared Co-NC anode …”
Section: Introductionsupporting
confidence: 54%
“…On the contrary, graphitic N sites display the weak adsorption of K + but enhance the conductivity of the carbon skeleton and promote the K-storage at a low potential range, which is beneficial for improving the energy density of PIBs . A similar potential effect from graphitic N sites was also observed by Chen et al who showed that for the prepared highly graphitic N-doped hard carbon, about 87% of capacity came from the contribution of the low potential region of below 1.0 V . In addition, significantly enhanced K + diffusion kinetics via reducing the diffusion energy barriers was also achieved in the prepared Co-NC anode …”
Section: Introductionsupporting
confidence: 54%
“…In this regard, corn stalk derived carbon has shown N-doped porous structure with SSA of 130.8 m 2 g -1 and N content of 2.36 at.%, leading to the higher specific capacitance of 402 mAh g -1 when compared to the material without N-doped (235 mAh g -1 ). This suggests that N doping could improve the specific capacity of biomass-derived carbons [100]. In LSBs, N dopants can also enhance storage sites and diffusion kinetics by enhancing chemisorption and delayed shuttling effects for polysulfide compounds [99].…”
Section: Heteroatoms-doped Carbonmentioning
confidence: 99%
“…26a)) and soft carbon (graphitisable carbon), emerge as promising candidates for anode materials. 335–359 This is attributed to their relatively low cost, high surface area, and ease of surface modification. Notably, graphite stands out as a viable option for achieving high-voltage KIBs, as its potassiation/depotassiation voltage plateau lies above 0.1 V versus K/K + (Fig.…”
Section: High-energy-density Potassium-ion Battery Full Cell Designmentioning
confidence: 99%